Pengaruh Kompensasi, Lingkungan Kerja, Budaya Organisasi dan Pemanfaatan Teknologi Informasi terhadap Motivasi Kerja Serta Dampaknya terhadap Kinerja - Musran Musran; Mohamad Makrus; Wargianto Wargianto (LPPM STIE PERTIBA Pangkalpinang, 2019)
This study aims to analyze the effect of compensation, work environment, organizational culture and the use of information technology on work motivation that has an impact on teacher performance by taking the object of research in Madrasah Aliyah Negeri (MAN) 1 Pangkalpinang. Analysis technique to test hypotheses using path analysis. The results of the study concluded that Compensation and Utilization of information technology affect work motivation, while the work environment and organizational culture do not affect work motivation. Furthermore, this study also concluded that work motivation has an effect and has an impact on teacher performance.